PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS SOSIAL PROVINSI NUSA TENGGARA TIMUR - Yohanes Soares (Mount Hope Management International Journal, 2024)
The purpose of the study was to determine the Influence of Motivation on Employee Performance at the Social Service Office of East Nusa Tenggara Province. Research method The research method used is a literature review technique that involves a series of steps to collect information from a number of previous articles found in Google Scholar and Science Direct databases. The results of the study are that employee motivation variables have a positive relationship with employee performance variables, this is evidenced by the r value of 0.407. In addition, motivation variables also affect the performance of employees of the Social Service of East Nusa Tenggara Province as evidenced by the coefficient of determination (adjusted R) produced is 16.5% while 83.5% is influenced by other factors not studied.